Influence of Visual and Vestibular Hypersensitivity on Derealization and Depersonalization in Chronic Dizziness - Toupet, Michel; Van Nechel, Christian; Hautefort, Charlotte; Heuschen, Sylvie; Duquesne, Ulla; Cassoulet, Anne; Bozorg Grayeli, Alexis (Frontiers in Neurology, 2019)
Objective: The aim of this study was to investigate the relation between visual and vestibular hypersensitivity, and Depersonalization/Derealization symptoms in patients with chronic dizziness. Materials and Methods: 319 adult patients with chronic dizziness for more than 3 months (214 females and 105 males, mean age: 58 years, range: 13–90) were included in this prospective cross-sectional study. Patients underwent a complete audio-vestibular workup and 3 auto questionnaires: Hospital Anxiety and Depression (HAD), Depersonalization/Derealization Inventory (DDI), and an in-house questionnaire (Dizziness in Daily Activity, DDA) assessing 9 activities with a score ranging from 0 (no difficulty) to 10 (maximal discomfort) and 11 (avoidance) to detect patients with visual and vestibular hypersensitivity (VVH, a score > 41 corresponding to mean + 1 standard deviation). Results: DDI scores were higher in case of VVH (6.9 ± 6.79, n = 55 vs. 4.2 ± 4.81, n = 256 without VVH, p < 0.001, unpaired t-test), migraine (6.1 ± 6.40, n = 110 vs. 4.0 ± 4.42, n = 208no migraine, p < 0.001, unpaired t-test), and motion sickness (6.8 ± 5.93, n = 41 vs. 4.4 ± 5.11, n = 277 no motion sickness, p < 0.01, unpaired t-test). Women scored DDI higher than men (5.1 ± 5.42, n = 213 vs. 3.9 ± 4.91, n = 105, respectively, p < 0.05, unpaired t-test). DDI scores were also related to depression and anxiety. DDI score was also higher during spells than during the basal state. Conclusion: During chronic dizziness, Depersonalization/Derealization symptoms seem to be related to anxiety and depression. Moreover, they were prominent in women, in those with visual and vestibular hypersensitivity, migraine, and motion sickness.